Increasing the perovskite cell performance using comparative layering method between PTAA and PEDOT: PSS layers - Vahdat Nazerian; Mehran Hosseinzadeh Dizaj; Amir Assari; Shahed Chehrdoust Shishvan; Fatemeh Shahnavaz; Tole Sutikno (Universitas Ahmad Dahlan, 2024)
Today, perovskite solar cells are introduced and used as a suitable alternative with high efficiency for silicon solar cells. The main problem of this type of cells until now has been mostly about their instability, because these materials that are used in perovskite solar cells are rapidly destroyed in reaction with air or their efficiency is greatly reduced. In this article, we increase the productivity to an acceptable amount and also increase its stability by using new high-quality synthesized materials and also by changing the manufacturing method of perovskite solar cells. Using the hole transport layers (HTLs), in the inverse planar perovskite solar cell structure, the effect of two layers of poly (triarylamine) (PTAA) and poly (3,4-ethylenedioxythiophene) (PEDOT): PSS as the bottom layer of the perovskite film on the morphology of the nanoparticles, the crystallinity of the perovskite layer and the photovoltaic parameters affecting the efficiency of the solar cell made in a single-step method were investigated. The result shows the PTAA layer has been very effective in controlling the morphology of the perovskite layer, so the efficiency reached to 23.9% while the maximum efficiency per solar cell based on PEDOT: PSS is 11.37%.